2015
DOI: 10.1007/s10195-015-0365-8
|View full text |Cite
|
Sign up to set email alerts
|

The use of a dual mobility cup in the management of recurrent dislocations of hip hemiarthroplasty

Abstract: BackgroundDislocation is one of the most frequent causes of failure of hemiarthroplasties of the hip, which is the most common treatment for femoral neck fractures in elderly patients. A revision with conversion to total hip arthroplasty is the gold standard in case of failure of closed reduction: however, the use of standard or modular components shows variable outcomes. The use of a dual mobility cup has been evaluated in patients with unstable implants, given the good outcomes obtained in primary and revisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 55 publications
0
29
0
1
Order By: Relevance
“…This is shown in several studies in which dual mobility components were used specifically to treat recurrent dislocation [3538]. Furthermore, dual mobility implants have also shown good reliability in unstable hemiarthroplasty revision converted to THA [40]. …”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…This is shown in several studies in which dual mobility components were used specifically to treat recurrent dislocation [3538]. Furthermore, dual mobility implants have also shown good reliability in unstable hemiarthroplasty revision converted to THA [40]. …”
Section: Resultsmentioning
confidence: 93%
“…Dual mobility cups are widely reported to reduce the risk of dislocation after rTHA [3340]. Dual mobility cups are designed with a 22- or 28-mm diameter femoral head component moving inside a larger polyethylene liner.…”
Section: Resultsmentioning
confidence: 99%
“…Reports on the prognosis of these treatments are lacking. Some scholars reported that convert to a THA with dual mobility cups in the treatment of a hemiarthroplasty recurrent dislocation had a very good outcome [19]. Early recurrent dislocation of BHA is a frequent indication for revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, less than − 10°of APP angle was considered to increase the anterior dislocation in standing position [3], therefore, our current patient was considered having the severe posterior pelvic tilt that resulted in anterior dislocation. In the previous reports, late postoperative dislocation of THA due to severe posterior tilt were treated by revision THA with elevated liner or optimization of cup anteversion [10] or use of dual mobility cup [11]. In our case, she underwent revision THA using a CT-based navigation system for the appropriate cup positioning in combination with a dual mobility cup.…”
Section: Discussionmentioning
confidence: 81%